1984
DOI: 10.1021/i100015a012
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol volatility in fermentation systems. Salt and metabolite effects

Abstract: The effect of dissolved species on the relative volatility of ethanol in fermentation systems is evaluated. New data are presented showing that the enhancement in volatility due to dissolved salts varies with ethanol concentration and is largest for the dilute ethanol concentrations typical in fermentation broths. Dissolved sugars and metabolites also affect relative volatility. The most commonly applied model of volatility enhancement does not incorporate the effect of ethanol concentration, and published enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…With another kind of molasses the factor was 2. It has been already shown that the ethanol volatility is affected by the sugar concentration (Maiorella et al 1984). In molasses many other components cause the volatility to increase: salts, proteins, etc.…”
Section: Gas Membrane Sensormentioning
confidence: 99%
“…With another kind of molasses the factor was 2. It has been already shown that the ethanol volatility is affected by the sugar concentration (Maiorella et al 1984). In molasses many other components cause the volatility to increase: salts, proteins, etc.…”
Section: Gas Membrane Sensormentioning
confidence: 99%
“…It has high cellulose and hemicelluloses content that can be readily hydrolysed into fermentable sugars. In terms of chemical composition, the straw predominantly contains cellulose (32-47%) hemicelluloses (19-27%) and lignin (5-24%) [4], [5], [6], [7]. The pentoses are dominant in hemicelluloses, in which xylose is the most important sugar (14.8-20.2%) [5], [8].…”
Section: Introductionmentioning
confidence: 99%